STRATEGY TO HANDLE RESISTANCE OF ANTIBIOTICS - Humaida, Rifka (Majority, 2014)
Abstract Antibiotics is a substances released by microorganisms and are acting as an antagonist agent against the growth and life of other microorganisms. Antibiotics are widely used by clinician to cure a lot of infectious diseases. The use of antibiotics during the last 5 decades has remarkably increasing. These, not only occur and becoming a problem in Indonesia, but also in a developed countries, such as United States. Extensive use of antibiotics, without a proper consideration of its rational use, may result in a strong selective pressure, and thus, eventually lead a bacteria to develop a resistance against a specific antibiotics. There are many things that are contributing to a resistance. This issue, if left untreated, will eventually become a disadvantage in terms of health an increase in the morbiditas and motilitas, economic, and social. Rational therapy, government regulation, and also public education is some key points in the strategy to handle the issue of antibiotic resistance. Keywords: antibiotic, resistance, strategy to handle, therapy Abstrak Antibiotik merupakan bahan yang dikeluarkan oleh mikroorganisme dan bersifat antagonik terhadap pertumbuhan dan hidupnya mikroorganisme lain. Antibiotik banyak digunakan klinisi untuk menangani berbagai penyakit infeksi. Pemakaian antibiotik selama 5 dekade terakhir mengalami peningkatan yang luar biasa, hal ini tidak hanya terjadi di Indonesia tetapi juga menjadi masalah di negara maju seperti Amerika Serikat. Penggunaannya yang luas mengakibatkan tekanan selektif yang kuat, dan secara konsisten menyebabkan bakteri resisten. Banyak hal yang mendukung terjadinya resistensi. Pada akhirnya masalah ini akan merugikan baik dari segi kesehatan terjadinya peningkatan angka morbiditas dan motilitas, ekonomi, dan sosial. Terapi rasional, regulasi pemerintah, juga edukasi masyarakat menjadi beberapa poin penting dalam stategi penanganan masalah resistensi ini. Kata kunci: antibiotik, resistensi, strategi penanganan, terapi